Hubungan Antara Komunikasi Interpersonal dan Iklim Organisasi dengan Stres Kerja Guru di Yayasan Pendidikan Singosari Deli Tua - Iranda Hari Fadhil; Kaiman Turnip; Suryani Hardjo (Universitas Medan Area, 2019)
This study aims to determine the relationship of interpersonal communication and organizational climate with the work stress of teachers at Singosari Delitua Education Foundation, the formulation of the proposed problem is whether there is interpersonal communication relationship with work stress, whether there is an organizational climate relationship with work stress and whether there is interpersonal communication organizational climate with work stress. The sample in this study amounted to 90 teachers. The sampling technique used is total sampling technique. Data collection model uses scale, that is interpersonal communication scale, organizational climate scale and work stress scale. Data analysis method used is multiple regression analysis. The results showed that 1). There is a significant relationship between interpersonal communication with work stress seen from linearity coefficient value (Rx1.y) = 0.592 with p = 0.000 0.050, it means there is interpersonal communication relation with job stress. Then 2). There is a significant correlation with organizational stress with work stress seen from linearity coefficient value (Rx2.y) = 0.643 with p = 0.000 0.050, it means there is organizational climate relationship with work stress. 3). There is significant correlation between interpersonal communication and organizational climate with work stress seen from linearity coefficient value (Rx1.x2.y) = 0.728 with p = 0.000 0.050, it means there is interpersonal communication relation and organizational climate with work stress.